2015
DOI: 10.1111/cup.12540
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil‐rich syphilis: a report of four cases

Abstract: The differential diagnosis for eosinophil-rich skin lesions often includes a drug reaction, allergic contact dermatitis and rarely, response to a helminth infection. However, many unrelated entities, such as infections, neoplasms and inflammatory dermatoses, can have a prominent eosinophilic infiltrate. Syphilis is classically associated with plasma cells, but other patterns of inflammation have been reported, including ulcerative, granulomatous and eosinophil-rich. Classic teaching might indicate that the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…Although the classical histological findings of syphilis include predominantly plasma cell infiltration, other findings including ulcerative, granulomatous and eosinophil-rich patterns have to be considered for the diagnosis of secondary syphilis. 8,15 Among the differential diagnoses in an HIV-infected patient, we considered pruritic popular eruption of HIV, prurigo nodularis, drug-induced eruption, arthropod bite reaction, nodular scabies, cutaneous lymphoproliferative disorders, and spread of cutaneous infection, in addition to secondary syphilis.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the classical histological findings of syphilis include predominantly plasma cell infiltration, other findings including ulcerative, granulomatous and eosinophil-rich patterns have to be considered for the diagnosis of secondary syphilis. 8,15 Among the differential diagnoses in an HIV-infected patient, we considered pruritic popular eruption of HIV, prurigo nodularis, drug-induced eruption, arthropod bite reaction, nodular scabies, cutaneous lymphoproliferative disorders, and spread of cutaneous infection, in addition to secondary syphilis.…”
Section: Case Reportmentioning
confidence: 99%
“…Although the classical histological findings of syphilis include predominantly plasma cell infiltration, other findings including ulcerative, granulomatous and eosinophil-rich patterns have to be considered for the diagnosis of secondary syphilis. 8,15…”
Section: Case Reportmentioning
confidence: 99%
“…Gambaran histopatologi pada sifilis sekunder dengan HIV dapat ditemukan eosinofil pada lapisan dermis. 24 Pada kasus ini didapatkan hasil pemeriksaan histopatologi yang diwarnai dengan HE, dengan sediaan jaringan yang diambil dari daerah telapak kaki didapatkan gambaran reaksi jaringan tipe psoriasiformis pada epidermis dengan infiltrat sel radang dengan kepadatan sedang yang terdiri dari limfosit dan didapatkannya gambaran endarteritis obliteran yang merupakan gambaran proliferasi lapisan intima arteri dan vena. Pemeriksaan ini dapat membedakan dengan psoriasis yang pada pemeriksaan histopatologi akan didapatkan adanya mikroabses Munro, mikroabses Kogoj, serta tidak didapatkan adanya papilomatosis.…”
Section: Case Reportunclassified
“…23 Pada sediaan ditemukan pula adanya eosinofil pada lapisan dermis yang sesuai dengan beberapa literatur yang menjelaskan mengenai eosinofil pada penderita koinfeksi sifilis sekunder pada HIV. 24 Spirochaeta akan lebih mudah terlihat bewarna coklat kehitaman pada pengecatan imunohistokimia terutama di epidermis, celah dermalepidermal, serta di dalam atau di sekitar pembuluh darah. 5 Pada sifilis sekunder dapat dilakukan pengecatan imunohistokimia menggunakan silver Levaditi, pewarnaan Warthin-Starry, teknik imunofluoresens.…”
Section: Case Reportunclassified
“…Due to the heterogeneity of etiology, it is not specific for any diseases. Although previous studies have not discussed syphilis in the differential diagnosis of ES as tissue eosinophilia in syphilis is an uncommon finding, Park and Kim 4 reported a case of secondary syphilis with numerous eosinophils and Rosa et al 5 reported four cases of eosinophil-rich syphilis, with HIV co-infection identified in two of the cases.…”
mentioning
confidence: 99%